El desierto era parecido a un paraíso: Aventuras posthumanas en una novela de G. Cabezón Cámara - Fleisner, Paula (2020)
In this paper we provide a reading of Gabriela Cabezón Cámara´s Las aventuras de la China Iron (2017) from a post-human materialistic aesthetic perspective, a line of research which considers that, in our post-anthropocentric and post-natural context, it has become essential to revisit the various logics of existence that populate the Earth. In other words, we attempt to think about the post/in-human space that opens up with the interaction, hybridization and co-emergence of everything that exists, a space in which human actors are present but instead of being the center of action inhabit a mix of diverse agencies. From this particular point of view we focus on two issues. Insofar as the narrator is a human animal, on the one hand the novel is understood as a horizontal and non-hierarchical description of the place of humanity on the planet, on the other hand, as the exploration of mutually contaminated powers of acting, thinking and feeling of what exists in general. According to this, the animal, the vegetable, and the mineral are no longer taxonomized in kingdoms but mixed in the unwired, ungovernable and fertile compost that the Argentinian desert could be. Considered as a rewriting of Martín Fierro, a foundational book of Argentina´s national identity, Cabezón Cámara´s novel can be read as the fable of a queer and holoentic "matria" that is the home to multiple species and kingdoms creatures.